2008
DOI: 10.1038/onc.2008.418
|View full text |Cite
|
Sign up to set email alerts
|

ILEI requires oncogenic Ras for the epithelial to mesenchymal transition of hepatocytes and liver carcinoma progression

Abstract: In human hepatocellular carcinoma (HCC), epithelial to mesenchymal transition (EMT) correlates with aggressiveness of tumors and poor survival. We employed a model of EMT based on immortalized p19 ARF null hepatocytes (MIM), which display tumor growth upon expression of oncogenic Ras and undergo EMT through the synergism of Ras and transforming growth factor (TGF)-b. Here, we show that the interleukin-related protein interleukin-like EMT inducer (ILEI), a novel EMT-, tumor-and metastasis-inducing protein, coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 41 publications
(65 reference statements)
3
78
1
Order By: Relevance
“…Unlike the results obtained with expression of activated RasV12, CMTM8 knockdown did not elevate the expression of ␣-smooth muscle actin (data not shown), which is a mesenchymal marker reported for EMT in hepatocyte-originated cell models (35). This difference may be due to incomplete knockdown with the available CMTM8 siRNAs, which are not capable of maintaining full knockdown during the course of extended EMT experiments.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Unlike the results obtained with expression of activated RasV12, CMTM8 knockdown did not elevate the expression of ␣-smooth muscle actin (data not shown), which is a mesenchymal marker reported for EMT in hepatocyte-originated cell models (35). This difference may be due to incomplete knockdown with the available CMTM8 siRNAs, which are not capable of maintaining full knockdown during the course of extended EMT experiments.…”
Section: Discussioncontrasting
confidence: 53%
“…We first tested the expression of EMT markers by indirect immunofluorescence and Western blotting. E-cadherin is an epithelial marker that functions in epithelial cell-cell adhesion and is down-regulated or mislocalized both in EMT cell models and at the invasive edge of some human tumor biopsies (2,15,16,34,35). In HepG2 cells with CMTM8 knockdown, E-cadherin was indeed down-regulated, which was verified by both immunofluorescence (Fig.…”
Section: Down-regulation Of Cmtm8 Induces An Emt-like Phenotypementioning
confidence: 72%
“…Earlier works have revealed that ILEI acts downstream of TGF-b to induce epithelial-to-mesenchymal transition of epithelial cells, whereas PANDER, which is cosecreted with insulin from pancreatic islet cells, is involved in regulation of insulin secretion and glycemic levels 28,36,37 . Expression of the ILEI transcript in human brain has been described 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of another EMT mediator, integrin-linked kinase (ILK), identifies hepatoma cell lines that are resistant to epidermal growth factor receptor-targeted therapies, and knocking down ILK restores sensitivity to these agents (21). EMT is also induced in neoplastic hepatocytes by TGF-β, IL-like EMT inducer (ILE1), and oncogenic Ras interactions that promote distant metastasis (22). Similarly, ectopic expression of Twist or Snail in hepatoma cell lines with low endogenous expression of these factors enhances cancer cell motility and invasiveness (12,17).…”
Section: Emt and Hccmentioning
confidence: 99%